IMPLEMENTASI STRATEGI PEMBELAJARAN CRITICAL INCIDENT (PENGALAMAN PENTING) PADA MATERI SUJUD SYUKUR, SAHWI, DAN TILAWAH KELAS VII DI SMP NEGERI 4 BUKITTINGGI - Jenysa Mulya Utami; Ulva Rahmi; Salmah (JIP: Jurnal Ilmu Pendidikan, 2024)
This research aims to make it easier for students to understand material about prostration of gratitude, prostration of sahwi, and prostration of recitations in the subjects of Islamic Religious Education and Character by using the Critical Incident learning strategy. The Critical Incident Strategy (Important Experience) is a strategy to activate students from the start of learning, namely a strategy in which students must remember and describe their past experiences in accordance with the topic of the material being presented, then the teacher delivers the material by connecting the experiences of the students. The approach concept used is a qualitative approach. The method used is descriptive analysis method. This research was conducted by researchers at SMP Negeri 4 Bukittinggi class VII using the Critical Incident learning strategy for students to more easily understand the material about prostration of gratitude, prostration of sahwi, and prostration of recitations and applying it in everyday life. By using this Critical Incident strategy, less active students now become active, where these students are asked about their experiences related to getting favors from Allah SWT, avoiding danger, doubting or forgetting the number of rak'ahs, and when hearing or reading the sajdah verse. So the learning is not too difficult for students to understand because in these learning activities it is based on students' experiences and through the Critical Incident strategy that students more easily understand the material that has been presented.